Promoting Transformative Learning Through Reading Fiction. (January 2015) - Hoggan, Chad; Cranton, Patricia
This article is a report on research into the role of fiction in promoting transformative learning in higher education settings. Participants were 131 undergraduate and graduate students from two universities in the United States. To determine the type of learning promoted by reading fiction, we performed qualitative analyses on participants' written reflections following a learning activity that included the reading of a fictional short story. Our major findings consisted of the following three categories: promoting change (with subcategories of promotes desire for change and stimulates change), new perspectives (with subcategories of opens eyes to new perspectives and opens new/more holistic perspectives), and fosters critical reflections. Supplementary findings were connections with personal experiences, emotional responses, and role models in the story. The types of learning described by our participants coincide with processes that promote transformative learning.